2020
DOI: 10.1007/s42341-020-00233-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Field Calculation and Structure Optimization of New Shield Ring of 1000 kV Nan-Jing Loop Transmission Line

Abstract: Considering the frequent breakage of the hard jumper shield ring in the strain tower of ultra-high voltage alternating current 1000 kV Nan-Jing Transmission Line, the theoretical and experimental studies on new shield ring were carried out in terms of mechanical properties; however, due to the structural changes of shield ring, the field characteristics should be calculated and analyzed. In accordance with the theory that there is no electric field in a metal conductor under electrostatic equilibrium, if there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Most of the studies found that there was electrostatic field calculation and optimization structure in power transformer bushing insulation, while some studies such as [11,12] found that there was condition assessment of high voltage bushing with solid insulation structure. Some studies such as [13,14] have found that electromagnetic forces and losses computation and design of power transformer bushings. By applying theory of electric field optimization based on charge simulation method, the author developed a computation program for electric field automatic optimization of an electrode profile with 3D dielectrics in axisymmetric field.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies found that there was electrostatic field calculation and optimization structure in power transformer bushing insulation, while some studies such as [11,12] found that there was condition assessment of high voltage bushing with solid insulation structure. Some studies such as [13,14] have found that electromagnetic forces and losses computation and design of power transformer bushings. By applying theory of electric field optimization based on charge simulation method, the author developed a computation program for electric field automatic optimization of an electrode profile with 3D dielectrics in axisymmetric field.…”
Section: Introductionmentioning
confidence: 99%